1994
DOI: 10.1001/archinte.154.12.1349
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patients' compliance with prescribed oral and inhaled asthma medications

Abstract: Comparison of medical record data with pharmacy claims data is an effective indirect measure of patients' compliance with prescribed oral theophylline and inhaled anti-inflammatory agents. Additional interventions must be pursued for patients with asthma regarding adherence to regimens for their prescribed inhaled anti-inflammatory agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
2
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 0 publications
3
55
2
2
Order By: Relevance
“…Although it was reported that daily dose and administration frequency might influence drug compliance [13,14,15], there were no data in support of this among our patient population. Recently, it was reported that taking LABA, LTRA, and OSRT in combination with ICS may enhance asthma management [23,24,25] and that both prescription of and compliance with these drugs are likely to improve the compliance of ICS themselves [26, 27]. In the present study, however, compliance of OSRT among FPdk users was significantly lower than that in FPdh users.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Although it was reported that daily dose and administration frequency might influence drug compliance [13,14,15], there were no data in support of this among our patient population. Recently, it was reported that taking LABA, LTRA, and OSRT in combination with ICS may enhance asthma management [23,24,25] and that both prescription of and compliance with these drugs are likely to improve the compliance of ICS themselves [26, 27]. In the present study, however, compliance of OSRT among FPdk users was significantly lower than that in FPdh users.…”
Section: Discussioncontrasting
confidence: 69%
“…In the present study, however, compliance of OSRT among FPdk users was significantly lower than that in FPdh users. Hence, since this result is at variance with previous observations [26, 27], it is difficult to interpret the possible influence of these factors from the available data. On the other hand, better compliance with FPdk could conceivably result in less necessity of OSRT use among FPdk users.…”
Section: Discussioncontrasting
confidence: 55%
“…This phenomenon is common to many chronic diseases like TB, bronchial asthma, rheumatic fever, hypertension, and psychiatric disorders[19,20,21]. A few studies on asthma have shown compliance levels ranging from 11 to 76%[22,23,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…The greater use of oral treatment in North America, including theophyllines, is likely to make a new oral therapy more acceptable there than it would be in Northern and Western Europe, as indeed suggested by a much-quoted study which compared patient compliance with treatment for oral and inhaled therapies. 84 The considerable investment of healthcare professionals in teaching patients how to use appropriate inhalation devices, particularly the very young and the very old, is another factor which is likely to influence the choice of therapy and delivery device. However, the convenience of a once-or twicedaily oral treatment that is targeted to receptors known to be involved in the asthmatic process has certain attractions.…”
Section: Public Perceptionsmentioning
confidence: 99%